Decomposing the effects of financial liberalization: Crises vs. growth - Ranciere, Romain; Tornell, Aaron; Westermann, Frank (Journal of Banking & Finance, 2006)
We present a new empirical decomposition of the effects of financial liberalization on economic growth and on the incidence of crises. Our empirical estimates show that the direct effect of financial liberalization on growth by far outweighs the indirect effect via a higher propensity to crisis. We also discuss several models of financial liberalization and growth whose predictions are consistent with our empirical findings.